2008
DOI: 10.1007/s11269-008-9269-1
|View full text |Cite
|
Sign up to set email alerts
|

Linking Performance and Collective Action—the Case of the Office du Niger Irrigation Scheme in Mali

Abstract: Increasing irrigation efficiency in irrigation schemes has always been high on the agenda of policy makers. Despite quite some 'social' experiments, whereby large portions of management were carried over to the farmer level, results often remained disappointing. This paper explores why this came about for a case study in the Office du Niger irrigation scheme in Mali. Since Irrigation Management Transfer, farmers are responsible for the tertiary level, but collective action for water management remains below ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
1
13
0
2
Order By: Relevance
“…Table 3 Total area cultivated with rice in la Saison, and the averages (l) of actual evapotranspiration, estimated fresh rice yields and water productivity for the Office du Niger as a whole, the five administrative zones and for the casiers located in the Niono zone Rice area (ha) Actual evapotranspiration (mm) Estimated rice yield (ton ha The standard deviation (r) and the coefficient of variation (c v ) for each parameter are presented also Irrig Sci (2010) 28:371-385 379 The c v of water consumption in the Office du Niger equals 0.092 (Table 3) which implies that the water consumption is spatially heterogeneous during la Saison. As mentioned before, water is abundantly available during this season, and crop growth appears not to be hampered by water shortages (Vandersypen et al 2006(Vandersypen et al , 2009. The values for c v found in the Office du Niger are similar to those measured in the Nile Delta in Egypt, which equalled 0.10 (Bastiaanssen 1997).…”
Section: Uniformitysupporting
confidence: 75%
“…Table 3 Total area cultivated with rice in la Saison, and the averages (l) of actual evapotranspiration, estimated fresh rice yields and water productivity for the Office du Niger as a whole, the five administrative zones and for the casiers located in the Niono zone Rice area (ha) Actual evapotranspiration (mm) Estimated rice yield (ton ha The standard deviation (r) and the coefficient of variation (c v ) for each parameter are presented also Irrig Sci (2010) 28:371-385 379 The c v of water consumption in the Office du Niger equals 0.092 (Table 3) which implies that the water consumption is spatially heterogeneous during la Saison. As mentioned before, water is abundantly available during this season, and crop growth appears not to be hampered by water shortages (Vandersypen et al 2006(Vandersypen et al , 2009. The values for c v found in the Office du Niger are similar to those measured in the Nile Delta in Egypt, which equalled 0.10 (Bastiaanssen 1997).…”
Section: Uniformitysupporting
confidence: 75%
“…An assessment study of IMT in Turkey by Kucu et al (2008), revealed that relative water supply had not shown any important change before and after transfer. Similarly, Vandersypen et al (2009) mentioned in the Office du Niger Irrigation Scheme in Mali that collective action at the intake level of the tertiary blocks improved irrigation efficiency, but was limited to 11 out of 36 tertiary blocks. These call for further improvement in post-IMT to have a better hydrological regime in the command.…”
Section: Better Hydrological Regime In the Commandmentioning
confidence: 97%
“…In Turkey, Yercan et al (2004) reported an increase in irrigated areas compared to those in the pretransfer period; another study on assessment of IMT (Kucu et al, 2008) revealed that the irrigation ratio increased by around 4% (from 58 to 62%) after the transfer. Results from a field study carried out in the Office du Niger Irrigation Scheme in Mali (Vandersypen et al, 2009) revealed that collective action at the intake level of the tertiary blocks improved irrigation efficiency by at least 14%, but was limited to 11 out of 36 tertiary blocks. Collective action made water allocation much better (26 out of 36 tertiary blocks), mitigating irrigation problems in the tertiary blocks.…”
Section: Impact On Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…That was stipulated in the first Contrat Plan in 1994. It was assumed that the Plan expressed everyone's interests, but performance did not significantly improve, because of a lack of incentive measures to bring about the desired collective action on the part of tenants (Vandersypen et al, 2007;Vandersypen et al, 2009).…”
Section: Contextmentioning
confidence: 99%